2008
DOI: 10.1259/bjr/30515892
|View full text |Cite
|
Sign up to set email alerts
|

Radiological detection of post-oesophagectomy anastomotic leak — a comparison between multidetector CT and fluoroscopy

Abstract: The purpose of this study was to directly compare CT with fluoroscopy for the diagnosis of occult anastomotic leak following oesophagectomy. Patients undergoing oesophagectomy and gastric conduit formation for the treatment of oesophageal cancer were eligible for inclusion. Imaging was performed 6-8 days post-operatively. Patients underwent multislice CT examination of the chest and abdomen with a bolus of oral contrast, followed by fluoroscopic water-soluble contrast swallow (with subsequent use of barium if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 12 publications
0
59
1
3
Order By: Relevance
“…Regarding the superiority of these exams no consensus has been reached. The study of Hogan et al [14] showed a Journal of Surgical Oncology higher specificity for CT compared to water-soluble contrast examination, but in the study of Upponi et al [15] the specificity was lower while the sensitivity was higher for CT. However, CT is preferred by patients and is more suitable in less mobile patients [14,15].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Regarding the superiority of these exams no consensus has been reached. The study of Hogan et al [14] showed a Journal of Surgical Oncology higher specificity for CT compared to water-soluble contrast examination, but in the study of Upponi et al [15] the specificity was lower while the sensitivity was higher for CT. However, CT is preferred by patients and is more suitable in less mobile patients [14,15].…”
Section: Discussionmentioning
confidence: 92%
“…The study of Hogan et al [14] showed a Journal of Surgical Oncology higher specificity for CT compared to water-soluble contrast examination, but in the study of Upponi et al [15] the specificity was lower while the sensitivity was higher for CT. However, CT is preferred by patients and is more suitable in less mobile patients [14,15]. Other investigators recommend the use of both contrast swallow and endoscopy to confirm a leak in case of clinical suspicion [16].…”
Section: Discussionmentioning
confidence: 92%
“…Esofagograma en proyecciones oblicua lateral (izquierda) y anteroposterior (derecha) en las que se identifica crecimiento auricular izquierdo (línea curva) que impronta y desplaza el esófago hacia la izquierda con nivel hidroaéreo (flecha punteada) por tránsito lento. cificidad en presencia de fugas de la anastomosis se acerca al 100% (30,31) (Figura 11).…”
Section: Tumores Benignos Del Esófagounclassified
“…Este estudio, además, provee información adicional sobre la presencia de aspiración y del adecuado vaciamiento del conducto usado para su reconstrucción (estómago o colon) (30,31) (Figuras 1 y 11).…”
Section: Tumores Benignos Del Esófagounclassified
See 1 more Smart Citation